The Effect of Stewing Basil Leaves (Ocimum Sanctum) and Ginger (Zingiber officinale rosc) combination on uric acid levels in patients with gout arthritis - MARETA DEA ROSALINE (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2019)
Background: Gout arthritis caused by high uric acid in the bloodstream and accumulation of uric acid crystals in tissues of the body that joint of inflammation leading to pain, redness, heat, and swelling. Basil leaves and ginger contains flavonoid compounds that can inhibit the formation of uric acid in the body.This research aim to analyze the effect of stewing basil leaves (Ocimum Sanctum) and ginger (Zingiber officinale rosc) combination on uric acid levels in patients with gout arthritis at Kranggan Public Health Center. Method: Quasy experimental with pre post-test control design. 50 respondents were involved and divided into treatment and control group. Combination Therapy of basil leaves and ginger is given 1 time for 7 days in the morning. Data were analyze used Paired T-Test and Independent T-Test. Result: There was significant the effect of basil leaves and ginger (Zingiber officinale rosc) combination on uric acid levels in patients with gout arthritis. Pretest and posttest outcome for treatment group generate p= 0.000 and comparison group generate p=0.009 with Independent T-test outcome p=0.004 (p<0,05). Discussion: This research is useful to complementary therapy as herbal therapy to decrease uric acid level. Keywords:, Basil Leaves, Ginger, Gout Arthritis, Uric Acid Levels